2020
DOI: 10.1021/acschembio.0c00180
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Channels Harness Membrane Potential to Concentrate Potassium in trk1Δtrk2Δ Yeast

Abstract: Many protein ion channels harness membrane potential to move ions in opposition to their chemical gradient. Deficiencies of such proteins cause several human diseases, including cystic fibrosis, Bartter Syndrome Type II, and proximal renal tubular acidosis. Using yeast as a readily manipulated eukaryotic model system, we asked whether, in the context of a deficiency of such protein ion channel function in vivo, small molecule channels could similarly harness membrane potential to concentrate ions. In yeast, Tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…While natamycin does not form classical pores for ions, in contrast to nystatin and AmpB [ 3 , 7 , 25 , 26 , 57 ], its membrane disturbing effect could potentially increase membrane access of (small) polar molecules. To test this notion, we employed a fluorescence assay based on quenching of the fluorescent phosphatidylcholine analogue NBD-PC by dithionite [58] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While natamycin does not form classical pores for ions, in contrast to nystatin and AmpB [ 3 , 7 , 25 , 26 , 57 ], its membrane disturbing effect could potentially increase membrane access of (small) polar molecules. To test this notion, we employed a fluorescence assay based on quenching of the fluorescent phosphatidylcholine analogue NBD-PC by dithionite [58] .…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we demonstrated that natamycin interferes with ergosterol- dependent activity of the lysine transporter Lyp1 reconstituted into model membranes [5] . In contrast to other polyenes, such as nystatin or amphotericin B (AmpB), natamycin does not form pores in lipid bilayers, such that a collapse of ion gradients across the plasma membrane (PM) is unlikely [ 3 , 6 , 7 ]. Natamycin may also have other mechanisms of action, such as inhibiting the fusion of yeast vacuoles or disruption of calcium homeostasis followed by loss of membrane potential, as shown for its action on leishmania parasites [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these results show that the PM is the target site for the polyene, and once the integrity of the cell membrane is compromised, natamycin enters the cell and stains internal compartments, such as the vacuole. Thus, even though natamycin is not known to form pores for ions in membranes 13,16,28 , it changes the membrane integrity and facilitates passage of small molecules, like PI. This finding is in accordance with our recent observation, that access of the aqueous quencher dithionite to the fluorescent phospholipid analogue NBD-PC is increased in the presence of natamycin in model membranes 18 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for nystatin, we found an even more pronounced ergosterol dependence of binding to yeast cells using our label-free imaging approach 35 . Both, nystatin and AmpB form sterol-dependent ion channels in membranes, while natamycin does not, and for AmpB ergosterol-specific interactions in lipid bilayers have been demonstrated using NMR spectroscopy 13,59,60 . Such divergent findings indicate fundamental differences in the mechanism by which various polyene molecules attack lipid membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation